Sensor based Management Information System for Dumpers for Indian Mines - Tiwari, M. S.; Uttarwar, Manish (Journal of Mines, Metals and Fuels, 2020)
Mining is a major economic activity in India and the industry is the backbone of the manufacturing and infrastructure sectors of the economy. It provides basic raw materials to several significant industries, including thermal, iron and steel, petroleum and natural gas, electrical and electronics equipment etc. We produce 87 minerals with good deposits of coal, iron ore, limestone, bauxite, manganese and chromite ores. Indian economy is one of the fastest growing economies in the world today. To fulfill plus 7% growth target, Indian mining industry has to increase its share in GDP from 2.4% to 6% (1). For this Indian Mining Sector has to grow at the rate of 10 to 12% annually. (2) Such voluminous increments can be met only by employing big size heavy earth moving machines (HEMM). Dumpers are the common choice in all types of mines for material movement. More than 4000 dumpers are being used in Indian mines. The cost of dumpers varies from Rs.1.0 crore for 35 tonnes to Rs.24 crore for 240 tonnes version (3). To meet the demand Bharat Earth Movers Limited (BEML) has started manufacturing of dumpers ranging from 60 tonnes to 205 tonnes (4). The availability and utilization percentage of dumpers is low as compared to other HEMM(5). CIL had carried out an internal study a few years ago which revealed that losses could be as high as Rs.50,000 if a 170 tonnes truck remained idle for half an hour. The figure would be double if the truck has larger capacity say, 240 tonnes. Hence there is a need for continuous monitoring of operational and machine parameters. Presently, only in large mines GPS based systems are being used to monitor such parameters. GPS based systems are not only costly but also requires qualified manpower to operate and maintain it (6). In small and medium mines monitoring is manual in nature. Manual method of data generation has its own limitations with respect to time and reliability. This calls for indigenous development of economical management information system (MIS) which could produce temper proof on line data. This research paper discusses one such management information system developed by the authors which is economical, easy to maintain and which produces continuous temper proof data.